2016
DOI: 10.1093/hmg/ddw324
|View full text |Cite
|
Sign up to set email alerts
|

Variants in angiopoietin-2 (ANGPT2) contribute to variation in nocturnal oxyhaemoglobin saturation level

Abstract: Genetic determinants of sleep-disordered breathing (SDB), a common set of disorders that contribute to significant cardiovascular and neuropsychiatric morbidity, are not clear. Overnight nocturnal oxygen saturation (SaO2) is a clinically relevant and easily measured indicator of SDB severity but its genetic contribution has never been studied. Our recent study suggests nocturnal SaO2 is heritable. We performed linkage analysis, association analysis and haplotype analysis of average nocturnal oxyhaemoglobin sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…An American study that evaluated genetic associations between 17 candidate genes, including Angpt2, and the development of lymphedema following treatment for breast cancer concluded that Ang2 rs1823375 has no significant involvement in lymphangiogenesis or angiogenesis [18]. Previous studies have reported that Angpt2 gene polymorphisms are associated with sleep-disordered breathing [25] and lung injury syndrome [13,26,27], indicating that Angpt2 could be a biomarker for lung disease. Another study, in an African American cohort, has reported that two SNPs in Angpt2 (rs1868554 and rs2442598) are significantly associated with acute lung injury pathogenesis and susceptibility [13].…”
Section: Discussionmentioning
confidence: 99%
“…An American study that evaluated genetic associations between 17 candidate genes, including Angpt2, and the development of lymphedema following treatment for breast cancer concluded that Ang2 rs1823375 has no significant involvement in lymphangiogenesis or angiogenesis [18]. Previous studies have reported that Angpt2 gene polymorphisms are associated with sleep-disordered breathing [25] and lung injury syndrome [13,26,27], indicating that Angpt2 could be a biomarker for lung disease. Another study, in an African American cohort, has reported that two SNPs in Angpt2 (rs1868554 and rs2442598) are significantly associated with acute lung injury pathogenesis and susceptibility [13].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options, however, are limited by a lack of knowledge of molecular pathways, including those that may be "druggable". Recent analyses of SDB traits have focused on common variants and identified several preliminary genome-level significant associations using GWAS, admixture mapping, and linkage approaches [ [11][12][13][14][15] ], but did not address gene-based or rare variant effects. Ten studies and over 21,000 individuals of multiple ancestries with WGS data at unprecedented resolution from the NHLBI TOPMed program combined with densely imputed data from other sources contributed to these results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a critical need to identify molecular pathways that could provide specific therapeutic targets. The need for overnight studies to phenotype SDB traits has limited the available sample size for genetic analyses, and only several common-frequency genome-wide analysis studies have been reported [11][12][13][14][15]. Increased statistical power may increase the genetic resolution of regions that may not be adequately tagged by current genotyping arrays due to population differences and/or reduced linkage disequilibrium with biologically relevant regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same group of authors used linkage analysis in the Cleveland Family Study to identify a strong association between polymorphism in the angiopoietin-2 gene (ANGPT2), an endothelial factor modulating vascular and inflammatory responses, and mean nocturnal Sa O 2 (9). Future large genetic studies are needed to replicate these findings (6).…”
Section: Genetics Of Osamentioning
confidence: 99%